Pathophysiological to Clinical Aspects of Head Injury: Narrative Literature Review - Hidayat, Rachmat (HM Publisher, 2022)
Head injury is a change in brain function or brain pathology, caused by external forces on the head. Changes in brain function consist of any period of loss or loss of consciousness, anterograde or retrograde amnesia, neurological deficits, or mental changes following a head injury. A study reported that the highest incidence of head injury was in the Americas, which was 1299 cases per 100,000 population, followed by Europe, which was 1012 cases per 100,000 population. The lowest incidence of head injury occurred on the African continent, which was 801 cases per 100,000 population. Based on these data, the overall incidence of head injuries in the world is 939 cases per 100,000 population with most of them being mild head injuries (55.9 million cases per year) and 5.28 million people experiencing severe head injuries.